Exploring the impact of big data driven technology towards e-recruitment efficiency and hr performance: The moderating effect of ethical technology - Abdalatif, Omima Abdalla Abass (International Journal of Economics, Business and Management Studies, 2025)
Although fast progression of artificial intelligence has compelled organizations to adopt disruptive technologies however organizations have been remained unsuccessful to gain maximum benefits from these technologies especially in the domain of human resource management. Owing to the proliferation of disruptive technologies this study encapsulates how big data driven human resource practices enhance e-recruitment efficiency. Research model was tested with empirical data retrieved from employees. Overall, 367 employees have participated in this e-recruitment research survey. Results illustrates that big data driven human resource practices, information quality, service quality, big data culture and digital maturity demonstrated substantial variance 75.2% in e-recruitment efficiency. Moreover, effect size analysis has disclosed large effect size of big data driven human resource practices and digital maturity in determining e-recruitment efficiency. This study has revealed that data driven human resource practices, digital maturity and big data service quality are core factors which enhance e-recruitment efficiency and hence these factors need managerial attention. Similarly, the moderating effect of ethical technology has established and revealed that higher intensity of ethical technology will stronger the relationship between e-recruitment efficiency and human resource performance. Therefore, policy makers could enhance recruitment efficiency and human resource performance by deploying ethical technology in human resource practices. This study is significant as it develops completely new research model backed by big data driven human resource practices and fills research gap between e-recruitment efficiency and human resource performance.